PERUBAHAN POLA KONSUMSI PANGAN RUMAHTANGGA RAWAN PANGAN - Ariani, Mewa; Hardono, Gatoet Sroe (PERSATUAN AHLI GIZI INDONESIA, 2005)
Food insecurity in households level is coverage multidimensional problems so that the rate of deteriorate is surely determined by negative interaction of many factors. This paper aims to analyze the changing in food consumption pattern of food insecure households due to the dynamic of situation of national economic using SUSENAS raw data 1996, 1999, and 2002. The food insecure households define as households who consump energy less than 80 % of energy sufficiency (2100 Kcal/cap/day). The result show that: (1) in 1996-2002 period, the share of food expenditure of food insecure households in out Java, in rural and households with agriculture as the main source of income always higher than those who are live in Java, in urban and who their main source of income come from non agriculture activities. When in crisis, the prosperity level of all type of households declined. But, in 2002 it raised back in line with the recovery of national economic (2) energy consumption of food insecure households is always low, only around 70 % of energy sufficiency, and (3) the level of protein consumption is only 40 gram/cap/day in average or about 83.3 % of protein sufficiency. Although there are a difference on protein consumption by island, region, and main source of income, but it is not significant. The same situation appears for the differentiation by time. As the implication, because the dynamic of national economic influenced the consumption pattern and the level of food insecurity so the government programs for economic recovery which deal with income rising should be conducted across all of the region. The priority target should be directed to households with low income who live in rural and who food insecure.Keywords: change, consumption pattern, food insecure households